2018
DOI: 10.1111/raq.12243
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the use of alternative protein sources for tilapia feeding

Abstract: The raising demand of fish for human consumption has caused a rise in fish cultivation to become a more intense activity and has increased the need for fish feed formulas for aquaculture. Tilapia are aquatic organisms with moderate protein requirements. One of the traditional ingredients used to develop protein diets is fish meal. Despite its high cost, this supply is of high demand for both aquaculture and terrestrial animals. Efforts to seek for alternative sources of conventional and unconventional proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 68 publications
0
30
0
2
Order By: Relevance
“…Though SBM has risen to one of the top‐traded commodities with a multitude of uses, soybean cultivation is highly concentrated geographically, with only four countries USA, Brazil, Argentina and China—accounting for almost 90% of world output while India being the fifth (Ash & Dohlman, 2012; Montoya‐Camacho et al, 2019; Ravindran et al, 2014; Thoenes & Trade, 2007;). In line with the substantial location‐wise variations in composition of SBM documented in previous studies, significant differences were observed in most of the chemical parameters of SBM tested during the study sourced from Argentina, Brazil, China, India and USA (García‐Rebollar et al, 2016; Ravindran et al, 2014; Van Kempen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Though SBM has risen to one of the top‐traded commodities with a multitude of uses, soybean cultivation is highly concentrated geographically, with only four countries USA, Brazil, Argentina and China—accounting for almost 90% of world output while India being the fifth (Ash & Dohlman, 2012; Montoya‐Camacho et al, 2019; Ravindran et al, 2014; Thoenes & Trade, 2007;). In line with the substantial location‐wise variations in composition of SBM documented in previous studies, significant differences were observed in most of the chemical parameters of SBM tested during the study sourced from Argentina, Brazil, China, India and USA (García‐Rebollar et al, 2016; Ravindran et al, 2014; Van Kempen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although PCs exert extensive antioxidant effects which have consequent health benefits, their inclusion in fish diets can modify feed intake, and have an impact on survival and growth performance of fish (El-Mesallamy et al, 2016;Omnes et al, 2017). Thus, given that the Nile tilapia (Oreochromis niloticus) is one of the most cultivated freshwater fish which can tolerate a multitude of environmental factors and exhibits a moderate protein requirement that can be derived from plant origin (Montoya-Camacho et al, 2019), it is a good model for the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean meal (SBM; 40%–51% crude protein) with a balanced amino acid profile as well as low cost and market availability standpoint, is considered as one of the most promising FM replacers in aquafeed industry (Huang, Ding, Dai, & Ma, ). However, the high non‐digestible carbohydrates (NDCs) and anti‐nutritional factors (ANFs) in SBM decrease its nutritional value and thereby affecting fish growth (Montoya‐Camacho et al, ). Various heating treatments such as toasting, extrusion, and pelletizing have been used to inactive or eliminate the NDCs and ANFs from SBM.…”
Section: Introductionmentioning
confidence: 99%
“…(NDCs) and anti-nutritional factors (ANFs) in SBM decrease its nutritional value and thereby affecting fish growth (Montoya-Camacho et al, 2018). Various heating treatments such as toasting, extrusion, and pelletizing have been used to inactive or eliminate the NDCs and ANFs from SBM.…”
mentioning
confidence: 99%